#Intersectionality: The Fourth Wave Feminist Twitter Community - Zimmerman, Tegan (Atlantis)

(untitled) (Mount Saint Vincent University, 2017)
This article analyzes the term “intersectionality” as defined by Kimberlé Williams Crenshaw in relation to the digital turn: it argues that intersectionality is the dominant framework being employed by fourth wave feminists and that is most apparent on social media, especially on Twitter.